Isolated renal pelvis rupture secondary to blunt trauma: Case report. (2015) - Taken, Kerem; Oncü, Mehmet Reşit; Ergün, Müslüm; Eryılmaz, Recep; Güneş, Mustafa
Highlights: A case, with isolated renal pelvis rupture due to blunt abdominal trauma. Clear urine output from the urinary catheter was seen in patient. Diagnosed a large rupture of renal pelvis by abdominal contrast enhanced CT. Isolated rupture of the renal pelvis causes delays in the diagnosis of the rupture. Only a few isolated cases of pelvis rupture with resultant extravasation have been described previously in literature. Surgical intervention should be warranted in emergency cases. Abstract: Introduction: Isolated rupture of the renal pelvis is a very rare condition and thus causes delays in the diagnosis of the rupture. It is most commonly seen in the setting of obstructive ureteric calculus. Other rare causes include neoplasms, trauma, and iatrogenic procedures. Diagnosis is usually established on computed tomography (CT) which demonstrates the extravasation of the contrast in the peripelvic, perinephric, or retroperitoneal collections. Presentation of case: A 27-year-old male patient was admitted to our hospital due to multiple traumas associated with motor vehicle accidents. The patient had clear urine output. A large pelvic rupture was detected by abdominal contrast-enhanced CT and after consulting with other departments, emergency repair of the renal pelvis was performed and a ureteral stent was implanted. Discussion: Only a few isolated cases of pelvis rupture with resultant extravasation have been reported in the literature. The treatment of pelvic rupture should be preceded by the removal of underlying causes, followed by conservative management. However, surgical intervention should be warranted in the emergency cases presenting with the symptoms that may impede the decision-making process and in the cases whose diagnosis cannot be clarified by radiological techniques. Conclusion: Renal pelvic injury must be considered in the differential diagnosis of blunt trauma. Surgical intervention may be necessary in some cases. We present a case who underwent surgery due to isolated renal pelvis rupture caused by blunt abdominal trauma.